PERFORMANCE OF SELF-CARE ACTIVITIES AMONG HEART FAILURE PATIENTS AT RANYA GENERAL HOSPITAL KURDISTAN –IRAQ - Mustafa, Rezan Ali; Amen, Muhammad Rashid (Journal of Sulaimani Medical College, 2021)
Background Heart failure is a major and growing public health problem worldwide that a negative impact on self-care. Self-care is a crucial task for controlling the negative consequences of the illness. Insufficient self-care leads to poor health outcomes and re-hospitalization. Objectives The objectives of the present study were to investigate the Self-care activities performance in patients admitted to Ranya general hospital and to explore the relationship between self-care and patients’ characteristics. Patients and Methods A convenience sample technique was used to enroll 86 patients with heart failure to present a descriptive study conducted at Ranya general hospital from January to November 2019. The data were collected through a questionnaire by direct interview. Participants, self-care was assessed with the Self-care of Heart Failure Index. Verbal consent and ethical approval were obtained, the data analyzed with descriptive and inferential statistical analysis. Results The findings revealed that the self-care maintenance, management, and confidence scores were: (52.9±8.8, 63.1±9.3), and (59.6±9.9) respectively. Higher scores indicate better self-care. None of the self-care subscales reached the self-care adequacy cut point of 70. The score of the self-care subscale was higher in better educated, obese patients who had low self-care maintenance and confidence, female. Longer duration and a more severe class of heart failure owned a greater score of self-care management, while self-care maintenance was higher in more severe cases. Conclusion Self-care performance was inadequate in heart failure patients; participants’ age, gender, educational status, BMI, and the severity of heart failure significantly associated with participants’ self-care performance.
Keywords: Self-Care; Heart failure; General Hospital